ผลของโปรแกรมการส่งเสริมการปฏิบัติสุขอนามัยส่วนบุคคลต่อความรู้ ทัศนคติ พฤติกรรมการป้องกันโรคอุจจาระร่วงในชุมชนชาวไทยภูเขาเผ่าม้ง อำเภองาว จังหวัดลำปาง - มลฑา เพ็ชรสุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Diarrhea is a common disease in local remote communities which is impossible for health care personnel to reach. This leads to the lack of knowledge and prevention of diarrhea among people in the community. This study was conducted to study the effects of the promoting personal hygiene practice program on knowledge, attitude, and behavior related to diarrhea prevention. Study sample were 30 Hmong hill tribe people in Ngao district, Lampang province. The program consisted of health education session and activities to promote community participation. Data were collected by questionnaire including 1) knowledge about diarrhea disease, 2) attitude, and 3) behavior related to diarrhea prevention. The data was analyzed using descriptive statistic and paired sample t-test. The research result found that after implementation of the program for 1 day and 1 month, participants had statistically significant higher average scores of knowledge, attitude and behavior related to diarrhea prevention, at level 0.05. Although there were increase of the number of people who had better knowledge and attitude related to diarrheal prevention, it was found that 50% of them had inaccurate behaviors. This especially related to hand washing before eating and milk preparation, or even let their children wash hands before eating. These poor practices pose a risk of getting diarrhea. Therefore a further study related to this issue needs to be developed. However, results from this study indicate a certain level of success of the promoting personal hygiene practices program. This program can be applied to other community areas to prevent such a common disease.